Feasibility study on creating secure and memorable password for Gen Y / Nor Zarina Zamri - Zamri, Nor Zarina (2016)
Passwords are the most commonly used authentication procedures for online web applications and systems based applications and to the system itself. Passwords are created by the users could be easier to memorize by relating to some sort of their regular activity or a name of near and dear ones, which obviously is easy to guess or crack by some means and could be a serious security concern. This study will seek to address the secure and memorable password for Gen Y. The researcher will conduct experiments to find the best approach which is can be decrease the human mind burden with created a secure and easy to remember password. Therefore, this research project aims to report on a password behavior of Gen Y and suggest the best approach to create secure and memorable password. In this research, researcher conducts the experiment to prove that the system policy is significant with the attempt to create and recall passwords. The experiment will conducts at private and government office by 38 participants. The data from the experiment which is from the database will be analyzed to collect password behavior of Gen Y and suggest the best approach to create a password. Even this research is achieved the objective, future research need to be conducted to evaluate the best approach has been suggested.